Remnant cholesterol, preinflammatory state and chronic kidney disease: association and mediation analyses - Yougen Yuan; Xiangming Hu; Shanghong Zhang; Weimian Wang; Bingyan Yu; Yingling Zhou; Yanqiu Ou; Haojian Dong (Renal Failure)
Blood lipid management is a key approach in the prevention of chronic kidney disease (CKD). Remnant cholesterol (RC) plays an important role in the development of multiple diseases via chronic inflammation. The aim of our study was to determine the relationship between RC and CKD and explore the role of inflammation in this relationship. The 7696 subjects from the Chinese Health and Nutrition Survey were divided into four subgroups according to the quartile of RC. The estimated glomerular filtration rate was calculated using the CKD Epidemiology Collaboration equation. Fasting RC was calculated as total cholesterol minus low-density lipoprotein cholesterol and high-density lipoprotein cholesterol. Logistic regression analysis was employed to evaluate the relationships between RC and CKD. Mediation analysis was undertaken to identify potential mediators of high-sensitivity C-reactive protein (hs-CRP) and white blood cells (WBCs). Of all participants, the mean age was 51 years, and the male accounted for 47.8%. The multivariable-adjusted odds ratios (95% CIs) for the highest versus lowest quartile of remnant cholesterol were 1.40 (1.10–1.78, p for trend = 0.006) for CKD. RC and preinflammatory markers have combined effect on CKD. The preinflammatory state, presented by increased hs-CRP or WBCs, partially mediated the association between RC and CKD with proportion of 10.14% (p = 0.002) and 11.65% (p = 0.012), respectively. In conclusion, this study suggested a positive relationship between RC and CKD, which was partially mediated by preinflammatory state. These findings highlight the importance of RC and inflammation in renal dysfunction. IMPACT STATEMENTWhat is already known on this subject?: Dyslipidemia plays an important role in the development of chronic kidney disease (CKD). Remnant cholesterol (RC), as a triglyceride-rich particle, can contribute to target organ damage, primarily through inflammatory pathways. However, the relationship between RC and CKD in the community-dwelling population, particularly the role of inflammation, is not yet fully understood.What do the results of this study add?: This study shows that RC was significantly associated with CKD. RC and preinflammatory status exhibit a combined effect on CKD. Preinflammatory state, presented by increased high-sensitivity C-reactive protein or white blood cells, partially mediated the association between RC and CKD.What are the implications of these findings for clinical practice and/or further research?: The study provides us with a better understanding of the role of RC and inflammation in kidney dysfunction and raises the awareness of RC in the management of CKD.